(untitled) (Fiep Bulletin - online, 2016)
The issue of learning disabilities is debated worldwide. Here in Brazil and throughout Latin America has gained alarming proportions. Prepare the student to learn how to learn. The attendance of students with learning disabilities (DAs) can be classified as generalized, to affect almost all learning (school and non-school), and how serious, are affected by several important aspects of personal development (motor, language, cognitive, etc.). From this point of view, this article comes up with a proposal for educators confront the situation through continuing education, ensuring the quality of student learning. Some proposals, such as assessment of student development, especially in the cognitive dimensions, metacognitive and linguistic characteristics of the specific learning difficulty that presents and the possible consequences on other aspects of his personality, such as self-esteem and anxiety. The purpose of this article is to educate the teacher that he must be aware of their professional competence as well as their attitudes and expectations about learning disabilities (DAs) and the future of the student. Proposed to analyze the educator context: immediate environmental conditions in which the teaching-learning processor (number of students, specific circumstances in which it presents the task, etc.) occurs; mediate and conditions (regarding linguistic, cultural and other social and cultural group of origin of the student), with the psychoeducational evaluation. Thus, the teacher rethinking their role as educators hold changes in pedagogical practice adapting to the particularities of the pupil using different assessment instruments, ie, teaching to think through flexible curriculum and not cast. This task of the teacher in the class should start integrating this approach and particularly to evaluate the characteristics of students with learning disabilities, difficulties and organize their knowledge, to enable their schemes, to communicate with their colleagues, and consequently, to share meanings and assign a meaning to their learning. Therefore, this important methodology can not forget the four characteristics that can ensure more positive outcomes to these relationships: 1 - Many of joint activities should be carefully planned; 2 - There should be opportunities for cooperation; 3 - The teacher must be vigilant and didactic knowledge of the subject taught: 4 - The facility to make learning simple, because the student with difficulties that need the educator, and it is our duty to craft.